Sentencing riot-related offending - Roberts, J; Hough, M (2013)
This article examines public attitudes to the sentencing offences associated with the rioting which took place in England in August 2011. Findings are based on a nationally representative survey of adults. The study uses a randomized split-sample experimental design to compare sentencing preferences for actual offences committed during the riots with preferences for similar offences committed under normal circumstances. The riot sub-sample generally 'sentenced' more severely than the non-riot sub-sample, but much less severely than the courts. The majority also thought that a non-custodial sentence with a reparative element was an acceptable alternative to custody. These trends suggest an unusual divergence of perspectives between the community and the courts: although the public are generally critical of the courts for leniency, with respect to non-violent offending during the riots, the latter appear more punitive. © 2012 The Author.